Dynamic Effect of Public Expenditure on Oil Producing Economy: An Empirical Evidence from Nigeria - Olanrele, Iyabo A. (Asian Journal of Economics and Empirical Research, 2020)
The paper examines the economic growth effect of government expenditure in Nigeria employing annual data from 1970 to 2017. Specifically, the study examines the short- and long-term effect of Federal Government total, recurrent, and capital expenditure on the real Gross Domestic Product (GDP). Different from the existing literature, the paper also shows the extent of oil sector integration, at the sectoral level, by investigating the effect of government expenditure on the agriculture and manufacturing sectors. The analysis was carried out using the Autoregressive Distribute Lag (ARDL) technique. Empirical results show that the aggregate government spending has a positive effect on the real GDP on the short and long-run. Mixed outcomes were realized when the effect of government expenditure on agricultural and manufacturing sector outputs were considered. In the short-run, total government expenditure cause agriculture sector output to decline. The long-run accumulated government spending leads to an increase in the agricultural sector output. The total government expenditure exerts a negative effect on the manufacturing sector output in the short-run. The effect was positive in the long-run. Outcomes from analyzing the differential effect of expenditure types on the real GDP show that capital expenditure had no impact on the real GDP, while government recurrent expenditure had a positive significant impact. Thus, efforts should be geared towards increasing capital spending for commensurate integration of oil benefits in the Nigerian economy.